Key Factors of Disruptive Innovation in Aerospace and Defence. Issue 3 (June 2022) - Rao, Shuktij Singh; Banik, Arindam; Khanna, Ashutosh; Philip, Deepu
Taking an idea or invention successfully from laboratory to the market is innovation. When such an innovation becomes so successful that it ultimately changes the social practices and thereby forces incumbent market leaders to shut shop, it becomes disruptive innovation (DI). Christensen proposed a framework to analyze an industry for DI and later analyzed five industries—aviation, education, healthcare, telecommunication, semiconductors & innovation overseas—using this framework. However, the business of aerospace and defence is different from conventional businesses and thereby requires additional considerations and modifications to the framework proposed by Christensen. This article focuses on the DI in aerospace and defence industry by developing an analytical framework that captures essential factors based on the original theory of Christensen; literature on and around it; known frameworks and studies of select successful cases of DI in aerospace and defence industry literature. Christensen's framework is analyzed and evaluated for its strengths and weaknesses and also its applicability to aerospace and defence business. Stakeholder analysis is also conducted, and empirical evidence of the factors is verified. A framework is then developed to analyze DI in the aerospace and defence industry.